Comparative Analysis of Treatment of Patients with Refractory Glaucoma of Various Stages by Microimpulse Transscleral Cyclophotocoagulation - I. E. Ioshin; A. I. Tolchinskaya; I. V. Maximov (Oftalʹmologiâ)
Objective: to analyze the results of treatment in patients with refractory glaucoma of various stages of the disease by microimpulse cyclophotocoagulation.Patients and methods. We examined 43 patients aged 68.5 ± 13.2 years with primary open-angle repeatedly operated subcompensated glaucoma (POAG) of advanced (13) and advanced (30) stages before and after performing MCPC (SUPRA 810 device, QuantelMedical, France) using standard laser parameters: energy W = 2000 MJ, 31.3 % — duty cycle, exposure time — 80 seconds per hemisphere.Results. The operation and postoperative period were uneventful. The hypotensive effect was achieved in all cases up to 6 months of follow-up. In the advanced stage of the disease, IOP decreased from 26.8 ± 7.8 mm Hg to an average of 17.1 ± 8.1 mm Hg (p < 0.05), and the amount of antihypertensive agents decreased from 2.89 ± 0.74 to 2.4 ± 0.6. in patients with advanced stage, IOP decreased from 29.9 ± 7.8 mm Hg to 21.0 ± 8.3 mm Hg (p < 0.05), and the amount of antihypertensive agents decreased from 3.1 ± 0.4 to 2.8 ± 0.5. The maximum corrected visual acuity (MCI) in all patients remained at the preoperative level during the entire follow-up period.Conclusion. Analysis of the results has shown that the use of microcyclophotocoagulation in patients with refractory glaucoma has not led to the development of postoperative complications, reduced intraocular pressure by 36.2 % from baseline, when developed and 29.8 % in advanced stages of the disease, reduced the number of antihypertensive drugs was 17 % in the second and 10 % at third stage and have not led to a decrease in visual function at 6 months follow-up. Thus, it is proved that the use of a diode laser in micro-pulse mode during microcyclophotocoagulation is a safe and effective method of treating refractory forms of glaucoma at various stages of the disease.